Struktur dan Fungsi Sosial Cerita Rakyat Legenda Setempat Batu Manda di Nagari Sungai Talang Kecamatan Guguak Kabupaten Lima Puluh Kota - Muhammad Ramadano; Nurizzati Nurizzati (Persona: Kajian Bahasa dan Sastra, 2023)
This study aims to describe: (1) the structure of the folklore of the Batu Manda legend in Negarian Sungai Talang, Guguak sub-district, Fifty-City District, (2) the social function of the folklore of the Batu Manda legend in Negarian Sungai Talang, Guguak sub-district, Fifty-City District. This type of research is research on local folklore legends using descriptive methods. The data in this study are the legendary folklore of Batu Manda in the Talang River Negarian, Guguak subdistrict, Fifty City District. Data were collected from informants through two stages, namely: (1) the stage of recording the legend of Batu Manda folklore, and (2) the stage of collecting data about the storytelling environment. Data about the storytelling environment were collected by recording, observation, and interview techniques. The data in this research were analyzed in four stages, namely: (1) the data identification stage, data collected from informants were identified through the data transliteration stage; (2) data classification or data analysis stage; (3) stage of discussion or conclusion of classification results or data analysis; (4) reporting stage. There are two findings in this research. First, the structure of the folklore of the Batu Manda legend in Negaraan Sungai Talang, Guguak sub-district, Fifty-City Regency, consists of: style of language, characters and characterizations, setting, plot, theme, message. Second, the function of the folklore of the Batu Manda legend in Nagari Sungai Talang, Guguak District, Fifty Cities Regency, consists of entertaining and educating. Entertaining and educational. Based on these findings, it turns out that folklore in the form of legends is still an oral literature that is highly trusted by the local community to this day.